Genomic characteristics and environmental distributions of the uncultivated Far-T4 phages - Roux, Simon; Enault, François; Ravet, Viviane; Pereira, Olivier; Sullivan, Matthew B. (Frontiers in Microbiology, 2015)
Viral metagenomics (viromics) is a tremendous tool to reveal viral diversity and ecosystem functional roles across ecosystems ranging from the human gut to the world's oceans. As with microbes however, there appear vast swaths of 'dark matter' yet to be documented for viruses, even among relatively well-studied viral types. Here, we use viromics to explore the 'Far-T4 phages' sequence space, a neighbor clade from the well-studied T4-like phages that was first detected through PCR study in seawater and subsequently identified in freshwater lakes through 454-sequenced viromes. To advance the description of these viruses beyond this single marker gene, we explore Far-T4 genome fragments assembled from 2 deeply-sequenced freshwater viromes. Single gene phylogenetic trees confirm that the Far-T4 phages are divergent from the T4-like phages, genome fragments reveal largely collinear genome organization, and both data led to the delineation of 5 Far-T4 clades. Three-dimensional models of major capsid proteins are consistent with a T4-like structure, and highlight highly conserved core flanked by variable insertions. Finally, we contextualize these now better characterized Far-T4 phages by re-analyzing 196 previously published viromes. These suggest that Far-T4 are common in freshwater and seawater as only 4 of 82 aquatic viromes lacked Far-T4-like sequences. Variability in representation across the 5 newly identified clades suggests clade-specific niche differentiation may be occurring across the different biomes, though the underlying mechanism remains unidentified. While complete genome assembly from complex communities and the lack of host linkage information still bottleneck virus discovery through viromes, these findings exemplify the power of metagenomics approaches to assess the diversity, evolutionary history, and genomic characteristics of novel uncultivated phages.